Anonymous reputation system - Chua, Wei Kiat (2017)
Current whistleblower applications are prone to simple denial of service attacks that can be carried out by sending multiple bogus reports. This is because current state of these applications does not allow journalist to check the legitimacy of these reports. Journalist must read through all these reports to obtain the correct report sent by a legitimate whistleblower which results in higher latency. This project aims to prevent this simple denial-of-service attack by introducing a one-time token that determines the level of trust of the report that it is attached to. Titled the Anonymous Reputation System (ARS), it utilizes the Ron Rivest, Adi Shamir and Leonard Adleman (RSA) algorithm to create a blind signature, using a client-side JavaScript, and sent it to the journalist together with the report. Once the report is read and approved by a Journalist, the blind signature will be signed with a signing key of certain level of trust and published on the list of signed blinded signature page. Journalist can obtain the token by unblinding these signed blinded signature and these tokens can be attached to their next report for higher creditability.